Figure of Speech Used in The Story of Layla and Majnun Novel by Nizami Ganjavi - Nimas Ayu Melati; Luqman Al Hakim (English Education Department Slamet Riyadi University Surakarta, 2021)
Understanding the meaning of a novel need literature study in semantics aspect especially in figurative language. This study aimed to identify and examine the meaning of figure of speech used in the novel The Story of Layla and Majnun Written by Nizami Ganjavi. This study focused on simile, metaphor, personification, hyperbole, metonymy, synecdoche, and irony form. The data was analyzed by applying descriptive qualitative method. The data collection used was documentation technique. Interactive model data of analysis used to analyze the data. From the result, this study was examined 76 sentences which was contained of figurative language. The data was analyzed one by one to identified the kind of figure of speech used and the meaning of them. The result of this study found 20 simile form, 13 metaphor form, 10 personification, 10 hyperbole form, 12 metonymy form, 3 synecdoche form. The most dominant figurative language used in this novel was form simile (26 %). This novel preserved the Bedouin culture and presented not only a romantic journey of love between humans, but also the Divine Love (Mahabbah). The researcher hope that readers would know about the study of linguistics. Especially in figurative language analysis to increase literary insight. Keywords: Semantics, Meanings, Figurative Language, Novel